Polycystic Ovary Syndrome - An Opportunity To Practice Proactive Preventive Medicine (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Abstract not availableJ Bangladesh Coll Phys Surg 2021; 39: 209-210